Profiling of organosulphur compounds using HPLC-PDA and GC/MS system and antioxidant activities in hooker chive (Allium hookeri). Issue 24 (16th December 2016) - Kim, Sunyoung; Kim, Dan-Bi; Lee, Sanghee; Park, Jisu; Shin, Dongbin; Yoo, Miyoung
Abstract: This study investigates the comprehensive organosulphur compounds and evaluation of antioxidant activities in Allium hookeri, called hooker chive. The non-volatile and volatile organosulphur compounds were determined by high-performance liquid chromatography-photodiode array detector (HPLC-PDA) and gas chromatography-mass spectrometry (GC-MS), respectively. Among 11 non-volatileorganosulphur compounds, methiin and cycloalliin were major compounds. A total of 42 volatile compounds were identified and allyl methyl sulphides and dimethyl sulphides were primarily volatiles. The total phenols ranged from 19.32 to 71.19 mg gallic acid equivalents (GAE)/g. The antioxidant capacities expressed IC50 values ranged from 9.59 to 38.54 mg/mL for DPPH radical scavenging activity and from 0.39 to 2.36 for ferric reducing antioxidant power assay. The results were proposed as useful tools for evaluating the nutraceutical of hooker chive. Abstract :